2013
DOI: 10.1142/s0217979213500471
|View full text |Cite
|
Sign up to set email alerts
|

Study of Physical Parameters on the Properties of Phononic Band Gaps

Abstract: In this work, we have introduced a comprehensive study concerning with the effects of some physical parameters on the dispersive properties of 1D phononic crystal (PnC). We have treated the propagation of elastic (in-plane) waves incident normally on 1D PnC. Based on the transfer matrix method, the reflection coefficients are calculated and plotted for the plane waves. We have studied many physical parameters effects on the properties of PnCs such as type of surrounding material, type of composites materials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Arafa et al . observed that the bonded materials have an effect on the band structure in the 1D PnCs 55 . Also, Denghui and Zhiyu studied the locally resonant PnC double panel structure consisting of a 2D periodic array of cylindrical locally resonant pillar connected between upper and lower plates from rubber layer 56 .…”
Section: Resultsmentioning
confidence: 95%
“…Arafa et al . observed that the bonded materials have an effect on the band structure in the 1D PnCs 55 . Also, Denghui and Zhiyu studied the locally resonant PnC double panel structure consisting of a 2D periodic array of cylindrical locally resonant pillar connected between upper and lower plates from rubber layer 56 .…”
Section: Resultsmentioning
confidence: 95%
“…If the interference was a constructive interference, it results in the formation of the stopped PC band gaps 64 , 65 . On the other side, when the interference is destructive, the resulted band is a transmission band 27 , 66 . The formula of the incident wave equation was written in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Since the vibrations occur very rapidly, there is no big chance to thermal energies to flow and the elastic constants measured by elastic waves propagation are changed adiabatically. The elastic constants are connected to the isothermal constants by the following relation [51][52][53][54][55],…”
Section: Temperature Influences On Pncsmentioning
confidence: 99%